Different effective promotional materials and strategies of SQUARE Pharmaceuticals Limited - Shakib, MD.Nazmus (BRAC University, 2017)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2017.